Combined compatibilization and plasticization effect of low molecular weight poly(lactic acid) in poly(lactic acid)/poly(3-hydroxybutyrate-co-3-hydroxyvalerate) blends - A. Amor; N. Okhay; A. Guinault; G. Miquelard-Garnier; C. Sollogoub; M. Gervais (eXPRESS Polymer Letters)
Improving overall properties of poly(lactic acid) (PLA) by blending it with another biobased polymer has been a strong field of research over the last years. In this study we demonstrate the synergetic effect of a small amount (between 0.1 and 1 wt%) of oligomer-like PLA (oLA) on the thermal, mechanical and gas barrier properties of the widely studied PLA-poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) blends (90–10 wt%). Films of PLA/PHBV/oLA blends were prepared via single-screw extrusion. oLA being miscible with both PLA and PHBV, its compatibilizing effect was demonstrated by a decrease of the interfacial tension, a slight shift in the Tgs of both polymers, and an increase in the elongation at break. It was also showed that oLA had a plasticizing effect on the PHBV dispersed phase, increasing its crystallinity rate. This resulted in a decrease in the permeability of the films while improving Young’s modulus.